Timonius kinabaluensis - Tsen, S.; Colin Ruzelion Maycock; Khoo, E.; Nilus, R.; Sugau, J.; Tanggaraju, S.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2020)
Timonius kinabaluensis is only known from Ranau district, Sabah. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are both 8 km2. The species is threatened by forest fire (Bukit hampuan forest reserve) with recurring fires occurring especially in the dry season. If these were to occur it could drive the species towards Critically Endangered or Extinct in the near future. Hence, it is assessed as Vulnerable. Timonius kinabaluensis is endemic to Sabah, Malaysia. It is restricted to the western and southern part of Kinabalu Park.